SYNTACTIC COMPETENCE OF TRANSFORMATION IN EMBEDDED SENTENCES OF SPOKEN BAHASA INDONESIA OF JUNIOR HIGH SCHOOL STUDENTS - Ida Nuraeni; Suparno Suparno; Titik Harsiati; Sumadi Sumadi (Universitas Negeri Makassar, 2020)
The purpose of this study was to describe the process of transformation and complexity of embedded sentences. This type of research is a one-site case study. The data source of this study was the verbal text of the students' utterances. The data, in the form of accepted sentences, were analyzed by using the interactive model of Milles & Huberman. The results shows that the transformation process in junior high school students’ embedded sentences of spoken Bahasa Indonesia were included the use of TTF, TTKLesap, TTNom, TTGanKlit, TSA, TSPelFN, and TSPelFVrules. The complexity of students’ sentence is shown by the use of the seven rules of transformation in a sentence. This finding shows that the eighth grade students have syntactic competence in the transformation of embedded sentences.